Optical wireless communication - Haas, Harald (Philos Trans A Math Phys Eng Sci, 2020)
Optical wireless communication has attracted significant interest recently in industry and academia. This special issue features a collection of inter-related papers with the intention to cover all necessary multidisciplinary challenges to realize optical wireless networks. We hope that this special issue will serve as a comprehensive reference and that it will be a resource which fosters many more new ideas for this rapidly emerging field. This article is part of the theme issue ‘Optical wireless communication’.